Mortality Risk in Older Inner-City African Americans - Malmstrom, Theodore K.; Andresen, Elena M.; Wolinsky, Fredric D.; Philip Miller, J.; Stamps, Kathryn; Miller, Douglas K. (Journal of the American Geriatrics Society, 2007)
OBJECTIVES: To investigate mortality risks in a sample of poor, inner‐city‐dwelling, older African Americans. DESIGN: Prospective cohort study. SETTING: St. Louis, Missouri. PARTICIPANTS: Six hundred twenty‐two African Americans aged 68 to 102 at the time of their 1992 to 1994 baseline interviews. MEASUREMENTS: Risk factors previously identified in the literature were examined for seven categories: demographic, socioeconomic, psychosocial, biomedical, disability and physical function, perceived health, and health services utilization. Vital status was ascertained through 2002. RESULTS: Three hundred eighty‐six subjects (62.1%) were deceased and 236 were alive (mortality higher than in matched controls). Significant risks for mortality were older age, male sex, annual income less than $10,000, cancer, cerebrovascular disease, dependencies in lower‐body function, and number of physician visits in the 12 months before baseline. CONCLUSION: In addition to improving the risk factors for stroke and malignant disease in this population, studies focused on improving lower‐body functioning may be warranted as a part of efforts aimed at enhancing longevity in older African‐American adults.